Optimal sampling and spatiotemporal change in epibenthos at a sub-Antarctic Marine Protected Area - Adams, Robyn (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2017. ENGLISH ABSTRACT: There have been notable regional and temporal changes in many biological systems around the Prince Edward Islands (PEI) in the Southern Ocean, but little work has focused on epibenthic assemblages. The aim of this study was to investigate spatial and temporal changes in the epibenthos, as they may be important indicators of change. During the austral summer of 2013 and 2015, a benthic towed camera system was employed to survey benthic habitats around Marion and Prince Edward Islands. This photographic sampling survey was conducted to align with a previous epibenthic photographic survey completed between 1984 and 1989. As marine photographic surveys have a propensity to underrepresent the species richness present, investigations into the optimal sampling intensity required per substrate type were conducted initially in order to ensure rigorous representative sampling. Historical photographic data of epibenthic assemblages in the upstream and downstream regions of the islands were then compared to data from the new photographic surveys to assess changes in regional species composition over time. Due to the various challenges associated with using underwater photography as a sampling method, identifying an optimal photographic sampling intensity for the epibenthos at the PEIs was imperative to this study. To achieve this, species-area relationships were used in conjunction with substrate type to determine the number of samples needed for given thresholds of species representation to be reached. The asymptotic richness estimator Chao 2 was used to compare the species richness detected in an area to a statistical estimation of the possible total species present. The point where species accumulation curves started to decelerate was identified as the point where a 20% increase in samples results in <5% increase in the number of new species observed. Points of deceleration were subsequently compared among substrate types. Substrate type was not found to ...